After Peterloo: Protest, Rebellion, and the Cato Street Conspiracy - Robert Poole (Caliban: French Journal of English Studies, 2021)
How close did Britain come to revolution in 1819-20? The ‘Peterloo massacre’ of August 1819 in Manchester was a landmark event in British radicalism. The wave of protests and disturbances which followed was stronger and more widespread than the radical campaign itself. It involved the whole spectrum of opposition from cautious Whig aristocrats through insurgent northern workers to London’s ultra-radicals, who attempted to assassinate the government in the Cato Street conspiracy of February 1820. This essay uses the wealth of material in the UK National Archives to examine the connections between these movements, and to assess how viable were plans for insurrection. It concludes that the London ultra-radicals, whilst giving the appearance of leading, had become isolated from the main radical movement by late 1819. The Cato Street conspiracy happened not because a national rising was expected but because one had already failed.